Cyclic carbonate-sulfate compound and application thereof, non-aqueous electrolyte and secondary battery
By using a cyclic carbonate-sulfate compound with an axisymmetric structure as an electrolyte additive in lithium-ion batteries, a compact solid electrolyte membrane is solved, and the performance instability and safety risks of lithium-ion batteries at high voltage and high temperatures are solved. Problem, improving the cycle stability and safety performance of the battery.
Patent Information
- Application Number
- CN202411699808.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Existing lithium-ion batteries have unstable performance and safety risks under high voltage and high temperature conditions, mainly due to the instability of the positive electrode material structure and the reduction of negative electrode lithium storage capacity and battery performance caused by metal ion migration.
The cyclic carbonate-sulfate compound with an axisymmetric structure is used as the electrolyte additive, and by forming a dense and uniform solid electrolyte membrane, the protection of the positive and negative electrode surfaces is improved, the impedance is reduced, and the high temperature stability of the battery is enhanced.
It significantly improves the cycle stability and safety performance of lithium-ion batteries, suppresses the risk of thermal runaway in the battery at high temperatures, and extends the battery's service life.
Smart Images

Figure CN119192165A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a cyclic carbonate-sulfate compound and application thereof, a non-aqueous electrolyte, and a secondary battery. Background Art
[0002] Lithium-ion batteries have been widely used in 3C digital products such as mobile phones and laptops, as well as new energy vehicles, due to their high operating voltage, wide operating temperature range, high energy density and power density, no memory effect, and long cycle life. In recent years, with the continuous development of 3C digital products, the battery industry has higher and higher requirements for high energy density of lithium-ion batteries. At the same time, for user considerations, good safety performance has become a basic requirement for batteries.
[0003] As the battery voltage gradually increases, the structural stability of the positive electrode material will deteriorate, and the transition metal in the positive electrode is prone to disproportionation reaction and dissolves in the electrolyte in the form of ions, causing the positive electrode structure to be destroyed and prone to thermal runaway risks under high temperature and high pressure. In addition, the dissolved metal ions migrate to the negative electrode interface, undergo ion exchange with the lithium in the negative electrode, occupy the negative electrode lithium insertion position, resulting in a decrease in the negative electrode lithium storage capacity and a deterioration in various battery performances, specifically manifested as: the battery produces gas, the internal resistance increases rapidly, and the capacity drops sharply. Battery gas production will cause the internal pressure to increase, and may further develop into dangerous situations such as battery explosion and combustion. The above situation is particularly obvious when the battery is under high temperature conditions.
[0004] There is a class of polycyclic carbonate sulfate compounds, which, when used as electrolyte additives, can participate in film formation on the positive and negative electrode surfaces during the battery formation stage. The solid electrolyte film formed has a certain improvement in the stability of battery materials, but there is still a large room for improvement in the improvement of the battery at high temperatures. The inventors have found that the spatial structure of polycyclic carbonate sulfate compounds has a certain influence on the battery performance improvement effect, but how to determine the influence of the spatial structure of polycyclic carbonate sulfate compounds on battery performance has a large technical obstacle. The main reason is that in the existing preparation method of polycyclic carbonate sulfate compounds, there is a situation where the chirality of the intermediate structure is unstable, and different stereoisomers are easily produced during the reaction process. In addition, there are multiple chiral carbons in the polycyclic carbonate sulfate compound, and there are many types of stereoisomers. When there are many types of stereoisomers, chiral separation becomes difficult, and it is difficult to further study the property differences of polycyclic carbonate sulfate compounds with different chiral structures. Summary of the invention
[0005] In view of the problems of insufficient high temperature performance and safety performance of existing high voltage lithium ion batteries, the present invention provides a cyclic carbonate-sulfate compound and its application, a non-aqueous electrolyte and a secondary battery.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a cyclic carbonate-sulfate compound, wherein the cyclic carbonate-sulfate compound comprises a compound shown in Chemical Formula 1, and the specific rotation of the cyclic carbonate-sulfate compound is [ α ] is -7.982°∙mL / (dm∙g)~+7.982°∙mL / (dm∙g); .
[0007] Optionally, the compound shown in Chemical Formula 1 includes a characteristic structure compound, and the characteristic structure compound is selected from the compound shown in Structural Formula 2 and / or the compound shown in Structural Formula 3, and the content of the characteristic structure compound in the compound shown in Chemical Formula 1 is ≥99wt%; .
[0008] Optionally, the characteristic structure compound is selected from the compound shown in Structural Formula 2.
[0009] Optionally, the characteristic structure compound is selected from the compound shown in Structural Formula 3.
[0010] Optionally, the specific rotation [ α ] The test conditions are: wavelength of 589nm, temperature of 20 degrees Celsius, solvent of acetonitrile, test tube length of 100mm, and concentration of cyclic carbonate-sulfate compound of 0.126g / mL.
[0011] Optionally, the cyclic carbonate-sulfate compound satisfies at least one of the following conditions: (I) In the cyclic carbonate-sulfate compound, the content of the compound represented by Chemical Formula 1 is ≥ 99 wt %; (II) The compound represented by the chemical formula 1 also includes stereoisomer impurities other than the characteristic structure compound, and the content of the stereoisomer impurities in the compound represented by the chemical formula 1 is ≤1wt%; (III) The content of chlorine in the cyclic carbonate-sulfate compound is ≤100 ppm.
[0012] Optionally, the cyclic carbonate-sulfate compound further comprises organic impurities, the mass content of the organic impurities is ≤1wt%, and the organic impurities comprise one or more of the following compounds: .
[0013] In another aspect, the present invention provides use of the cyclic carbonate-sulfate compound as described above as an electrolyte additive.
[0014] In yet another aspect, the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises the cyclic carbonate-sulfate compound as described above.
[0015] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the cyclic carbonate-sulfate compound is 0.01% to 5%.
[0016] In another aspect, the present invention provides a secondary battery comprising the non-aqueous electrolyte as described above.
[0017] According to the cyclic carbonate-sulfate compound provided by the present invention, in order to improve the film-forming quality of the additive during the first charge and discharge process of the battery, the inventors found in previous studies that a polycyclic sulfate (as shown in Chemical Formula 1) having a carbonate skeleton in the middle and sulfate rings on both sides is conducive to forming the spatial structure of the solid electrolyte membrane on the surface of the positive and negative electrodes, and has been reported in previously applied patents. Based on further research, the inventors found that there are multiple chiral configurations in the compound shown in Chemical Formula 1, and the different chiral configurations of the compound shown in Chemical Formula 1 have certain differences in film-forming performance, and also interfere with each other. Disturbance, thereby affecting the orderliness of the solid electrolyte film on the surface of the positive and negative electrodes. Through purification and testing of different chiral configurations of the compound shown in Chemical Formula 1, it is found that the non-axisymmetric chiral configuration of the compound shown in Chemical Formula 1 has a certain randomness during film formation because of the different chemical environments of the sulfate esters on both sides, which causes the newly formed film to be unable to cover the active sites in the most compact way, resulting in more exposed active sites in the formed film, and the positive and negative electrode materials are still not effectively protected. They are broken and decomposed under the continuous electrochemical process or the continuous increase in thermal shock, thereby causing the battery to fail in cycle or be damaged by thermal shock. When the content of the characteristic structure compound selected from the compound shown in Structural Formula 2 and / or Structural Formula 3 is high in the compound shown in Chemical Formula 1, the solid electrolyte film formed is more compact and uniform, and the stability under high temperature conditions is improved, and the impedance is reduced. It is speculated that the control of the film formation process brought about by its axisymmetry. After the axisymmetric characteristic structure compound and lithium ions are coordinated, under the action of the electric field, an electrochemical reaction occurs at the electrode active site to produce the corresponding inorganic salt-organic complex. At the same time, due to the axial symmetry of this type of molecules, when the lithium ion-additive complex formed on the electrode forms a film again, the two sulfates have similar complexing properties for lithium ions. Therefore, the spatial structure after complexation, the spatial conformation of the molecular complex and the influence of the resistance of the surrounding solvent molecules on it tend to be similar. At the same time, it will be guided by the already formed SEI or CEI film, so that a relatively regular and more resilient organic-inorganic composite film can be formed in the same or similar way, effectively covering up most of the active sites and preventing them from further migrating to the counter electrode with other active ingredients in the electrolyte or positive and negative electrode materials to undergo electrochemical reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the nuclear magnetic resonance test hydrogen spectrum (1HNMR) of the carbonate polyol provided in Preparation Example 1 of the present invention, and the deuterated reagent is deuterated DMSO (the horizontal axis f1 (ppm) in the figure represents the chemical shift, and the vertical axis represents the absorption peak intensity, the same below).
[0019] Figure 2 is the carbon spectrum of the carbonate polyol provided in Preparation Example 1 of the present invention ( 13CNMR), deuterated reagent: deuterated DMSO; Figure 3 The nuclear magnetic resonance test hydrogen spectrum of the cyclic carbonate-sulfate compound provided in Preparation Example 1 of the present invention ( 1 HNMR), deuterated reagent: deuterated acetonitrile; Figure 4 The carbon spectrum of the cyclic carbonate-sulfate compound provided in Preparation Example 1 of the present invention is measured by NMR ( 13 CNMR), deuterated reagent: deuterated acetonitrile; Figure 5 The nuclear magnetic resonance test hydrogen spectrum of the cyclic carbonate-sulfate compound provided in Preparation Example 1 of the present invention ( 1 HNMR), deuterated reagent: deuterated DMSO; Figure 6 The carbon spectrum of the cyclic carbonate-sulfate compound provided in Preparation Example 1 of the present invention is measured by NMR ( 13 CNMR), deuterated reagent: deuterated DMSO; Figure 7 is a crystal spatial structure diagram of the compound represented by structural formula 2 (Example 1); Figure 8 is an ellipsoidal diagram of the compound represented by structural formula 2 (Example 1); Fig. 9 is a comparison diagram of powder diffraction of structural formula 2 and simulated diffraction of single crystal (Example 1, in the figure, the ordinate Intensity (au) represents the relative intensity of the diffraction peak, the abscissa 2θ (degrees) represents the 2θ angle, the upper right corner As synthesized represents the powder diffraction peak of the sample of structural formula 2, and Simulated represents the simulated diffraction peak of the single crystal of structural formula 2); Fig.10 The nuclear magnetic resonance test hydrogen spectrum of the cyclic carbonate-sulfate compound provided in Preparation Example 3 of the present invention ( 1 HNMR), deuterated reagent: deuterated acetonitrile; Fig.11 The carbon spectrum of the cyclic carbonate-sulfate compound provided in Preparation Example 3 of the present invention is measured by NMR ( 13 CNMR), deuterated reagent: deuterated acetonitrile; Fig.12 It is an electron microscope observation picture of the positive electrode sheet provided in Example 3 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0020] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] One embodiment of the present invention provides that the cyclic carbonate-sulfate compound includes the compound shown in Chemical Formula 1, and the specific rotation of the cyclic carbonate-sulfate compound is [ α ] is -7.982°∙mL / (dm∙g)~+7.982°∙mL / (dm∙g); .
[0022] When the specific rotation of the cyclic carbonate-sulfate compound [ α ] is -7.982°∙mL / (dm∙g)~+7.982°∙mL / (dm∙g), the molecular structure of its characteristic structural compound has a higher symmetry, which is beneficial to the formation of a regular and stable solid electrolyte interface film on the surface of the positive and negative electrodes during the battery formation stage, thereby improving the electrochemical performance of the secondary battery.
[0023] In some embodiments, the compound represented by Chemical Formula 1 includes a characteristic structure compound, and the characteristic structure compound is selected from the compound represented by Structural Formula 2 and / or the compound represented by Structural Formula 3, and the content of the characteristic structure compound in the compound represented by Chemical Formula 1 is ≥99wt%; .
[0024] Since there are multiple chiral carbons in the compound shown in Chemical Formula 1, there are multiple chiral configurations in the compound shown in Chemical Formula 1, and the different chiral configurations of the compound shown in Chemical Formula 1 have large differences in film-forming properties and interfere with each other, thereby affecting the orderliness of the solid electrolyte film on the positive and negative electrode surfaces.
[0025] Through purification and testing of different chiral configurations of the compound shown in Chemical Formula 1, it is found that the non-axisymmetric chiral configuration of the compound shown in Chemical Formula 1 has a certain randomness to the sulfates on both sides during film formation, which causes the newly formed film to be unable to cover the active sites in the most compact way, resulting in more exposed active sites of the formed film, and the positive and negative electrode materials are still not effectively protected, which may be broken and decomposed under the continuous electrochemical process or the continuous increase of thermal shock, thereby causing the battery cycle failure or thermal shock damage. When the content of the characteristic structure compound selected from the compound shown in Structural Formula 2 and / or Structural Formula 3 is high in the compound shown in Chemical Formula 1, the solid electrolyte film formed is more compact and uniform, and the stability under high temperature conditions is improved. It is speculated that the control of the film formation process brought about by its axisymmetry. After the characteristic structure compound with axisymmetry is coordinated with lithium ions, an electrochemical reaction occurs at the electrode active site under the action of the electric field to produce the corresponding inorganic salt-organic complex. At the same time, due to the axial symmetry of this type of molecules, when the lithium ion-additive complex that is about to form a film on the electrode forms a film again, since the two sulfates have the same complexing properties for lithium ions, the spatial structure after complexing, the spatial conformation of the molecular complex and the influence of the resistance of the surrounding solvent molecules on it are the same. At the same time, it will be guided by the already formed SEI or CEI film, and thus can form a relatively regular and more resilient organic-inorganic composite film in the same way, effectively covering up most of the active sites and preventing them from further migrating to the counter electrode with other active ingredients in the electrolyte or positive and negative electrode materials to undergo electrochemical reactions.
[0026] Among them, if measured Figure 7 And measured Figure 8 As shown, the structure 2 is two-fold rotation axis symmetric (abbreviated as "axis symmetric"). The compound shown in the structure 2 is a monoclinic system, which is characterized by no higher-order symmetry axis, the b axis is the only axis, and there are no more than one secondary symmetry axis and symmetry plane. The b axis is orthogonal to the a axis and the c axis, while the a axis is oblique to the c axis, with an axis angle α=γ=90°, β≠90°, and an axis unit a≠b≠c. And the space group of the structure 2 is P21, and its symmetry elements include a two-fold rotation axis and a slip plane, that is, the symmetry operation of the structure 2 includes a two-fold rotation around the b axis and a slip plane perpendicular to the b axis.
[0027] The molecular formula of structural formula 3 is the same as that of structural formula 2, and they are mirror images in stereostructure. Therefore, the compound represented by structural formula 3 plays almost the same role as the compound represented by structural formula 2 in the electrolyte as an additive. The compound represented by structural formula 2 and the compound represented by structural formula 3 can be distinguished by testing the specific rotation.
[0028] In a preferred embodiment, the specific rotation of the cyclic carbonate-sulfate compound is [ α] is -7.724°∙mL / (dm∙g)~+7.724°∙mL / (dm∙g).
[0029] In a more preferred embodiment, the specific rotation of the cyclic carbonate-sulfate compound [ α ] is -7.525°∙mL / (dm∙g)~+7.525°∙mL / (dm∙g).
[0030] In a more preferred embodiment, the specific rotation of the cyclic carbonate-sulfate compound [ α ] is -7.310°∙mL / (dm∙g)~+7.310°∙mL / (dm∙g).
[0031] In a preferred embodiment, in the compound represented by Chemical Formula 1, the content of the characteristic structure compound is ≥99wt%.
[0032] When the content of the characteristic structure compound in the compound shown in Chemical Formula 1 is higher, it is more conducive to improving the orderliness of the formed solid electrolyte membrane and avoiding the influence of other isomer compounds.
[0033] Compared with a mixture of the compound shown in Structural Formula 2 and the compound shown in Structural Formula 3, when the characteristic structural compound is selected from a single chiral configuration, it is more conducive to improving the thermal shock resistance of the formed solid electrolyte membrane, indicating that the characteristic structural compound with a single chiral configuration is related to improving the orderliness of the solid electrolyte membrane.
[0034] In some embodiments, in the cyclic carbonate-sulfate compound, the content of the compound represented by Chemical Formula 1 is ≥ 99 wt %.
[0035] In some embodiments, the compound represented by Chemical Formula 1 further includes stereoisomer impurities other than the characteristic structure compound, and the content of the stereoisomer impurities in the compound represented by Chemical Formula 1 is ≤1 wt %.
[0036] In a preferred embodiment, the content of stereoisomer impurities in the compound represented by Chemical Formula 1 is ≤0.5 wt %.
[0037] The sources of the stereoisomer impurities are mainly from two aspects. On the one hand, the stereoisomer impurities contained in the preparation raw materials. For example, when D-mannitol is used as the initial raw material to prepare the compound shown in Structural Formula 2, the sorbitol or other types of stereoisomers contained therein may be reflected in the final product of the synthesis reaction; on the other hand, they are generated during the preparation process. For example, the stereo configuration of some intermediates is unstable, resulting in chirality inversion and other phenomena, and stereoisomer impurities appear in the prepared compound shown in Structural Formula 2.
[0038] By reducing the impurity content, it is helpful to reduce the problem of insufficient density of the solid electrolyte membrane caused by the presence of stereoisomers.
[0039] In some embodiments, the content of chlorine in the cyclic carbonate-sulfate compound is ≤100 ppm.
[0040] The source of chlorine is mainly due to chlorine-containing impurities carried in the reaction raw materials or solvents. The presence of chlorine in the cyclic carbonate-sulfate compound has a great influence on its performance as an electrolyte additive. Although chlorine is usually formed as a substituent in the impurities of the cyclic carbonate-sulfate compound, under electrochemical conditions, chlorine-containing impurities are unstable and easily decompose to form free chlorine. Free chlorine in non-aqueous electrolytes can easily induce corrosion of the positive electrode collector and dissolution of transition metal ions in the positive electrode material. Therefore, it is necessary to control the content of chlorine in the cyclic carbonate-sulfate compound to reduce the impact.
[0041] In some embodiments, the cyclic carbonate-sulfate compound further includes organic impurities, the mass content of the organic impurities is ≤1%, and the organic impurities include one or more of the following compounds: .
[0042] The organic impurities include impurities derived from unreacted raw materials, such as etc., or impurities caused by ester exchange at other positions in step S1, such as etc., are not conducive to the uniformity of the solid electrolyte membrane on the surface of the positive and negative electrodes, thereby forming defects on the solid electrolyte membrane, leading to problems such as uneven thickness of the solid electrolyte membrane. By controlling the purification conditions and the reaction yield, the content of the organic impurities can be reduced, which is beneficial to reducing the defects on the solid electrolyte membrane, ensuring the thermal shock resistance of the solid electrolyte membrane, and improving the safety performance of the battery.
[0043] Another embodiment of the present invention provides the use of the cyclic carbonate-sulfate compound as described above as an electrolyte additive.
[0044] Another embodiment of the present invention provides a method for preparing the cyclic carbonate-sulfate compound as described above, comprising the following steps: S1. Mixing a hexahydric alcohol, an alkaline catalyst, a carbonate and a low-hydric alcohol to obtain a carbonate polyol, wherein the hexahydric alcohol includes a compound shown in Structural Formula 4 and / or a compound shown in Structural Formula 5, the carbonate polyol includes a compound shown in Structural Formula 6 and / or a compound shown in Structural Formula 7, and the low-hydric alcohol is a monohydric alcohol and / or a dihydric alcohol; .
[0045] S2. Reacting carbonate polyol with N,N'-sulfuryldiimidazole to obtain a compound shown in Chemical Formula 1.
[0046] The reaction route is as follows: .
[0047] In the preparation method provided by the present invention, the preparation method of step S1 has a certain similarity with patent KR1020190116899, and carbonate is first subjected to transesterification reaction with hexahydric alcohol to prepare carbonate polyol. Since there are multiple hydroxyl groups in the hexahydric alcohol, and they are respectively located on different carbons, in the transesterification reaction, carbonate will undergo transesterification reaction with any hydroxyl group to obtain different types of reaction products, resulting in reduced product yield and subsequent purification difficulties. Therefore, the present preparation method adds low-alcohols in step S1. When low-alcohols are present, the reactivity of the hydroxyl groups on the two middle carbons in the transesterification reaction can be greatly improved, while suppressing the reactivity of the hydroxyl groups on both sides of the hexahydric alcohol, thereby ensuring that the prepared reaction product is mainly carbonate polyol, which can greatly improve the reaction yield and reduce the difficulty of purification.
[0048] In the process of further preparing the compound shown in Chemical Formula 1 from carbonate polyol, the existing preparation method has the problem that the chiral structure of the intermediate is unstable and the chiral inversion phenomenon occurs. The chiral structure of the reaction intermediate is unstable, so that its chiral structure undergoes chiral inversion during the reaction to obtain different stereoisomers, affecting the chiral configuration purity of the final product. In order to solve this technical problem and ensure the consistency of the stereo configuration of the compound shown in Chemical Formula 1, the present invention uses N, N'-sulfuryl diimidazole to react with carbonate polyol (Structural Formula 6 or 7) to obtain the target product; using a non-protonic solvent with a small dielectric constant, avoiding the configuration inversion of the reaction process that may be caused by a strong polar solvent / protic solvent, using N, N'-sulfuryl diimidazole has greater steric hindrance, which is conducive to the maintenance of the chiral configuration, and can maintain the spatial configuration of carbonate polyol (Structural Formula 6 or 7) to obtain the characteristic structure compound shown in Structural Formula 2 or Structural Formula 3. And the content of the characteristic structure compound shown in Structural Formula 2 and / or Structural Formula 3 is finally obtained to be ≥99wt%.
[0049] In some embodiments, in step S1, the molar ratio of carbonate to hexahydric alcohol is 5:1-10:1.
[0050] The theoretical reaction molar ratio of carbonate to hexahydric alcohol is 1:1. In the present preparation method, excessive addition of carbonate is beneficial to accelerate the reaction. However, the addition amount of carbonate should not be too high. Too high carbonate will easily increase the probability of substitution of hydroxyl groups at both sides and generate impurities.
[0051] In some embodiments, in step S1, the molar ratio of the low-alcohol to the carbonate is 1:1-5:1.
[0052] The low-alcohol plays a role in promoting the reactivity of the hydroxyl group in the middle position of the hexyl alcohol, inhibiting the reactivity of the hydroxyl groups on both sides of the hexyl alcohol, and inhibiting side reactions in the ester exchange reaction; when the addition amount of the low-alcohol is too low, it is difficult to ensure the inhibition of side reactions, resulting in the reaction between the hydroxyl groups at non-predetermined positions and the carbonate ester, forming a large number of unnecessary by-products; but since the low-alcohol itself is also a reaction product of the carbonate ester and the hexyl alcohol, when the addition amount of the low-alcohol is too high, it will inhibit the forward progress of the reaction, resulting in an extension of the time required for the reaction, affecting the production efficiency.
[0053] In the step S1, the addition of the alkaline catalyst is beneficial to improving the reaction activity between the hexavalent alcohol and the carbonate.
[0054] In some embodiments, the alkaline catalyst includes one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, lithium carbonate, sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium tert-butoxide, triethylamine, and pyridine.
[0055] In some embodiments, the added mass of the alkaline catalyst is 0.1% to 0.8% of the mass of the hexyl alcohol.
[0056] When the amount of the alkaline catalyst added is within the above range, it is beneficial to ensure the alkaline environment required for the reaction, while avoiding the difficulty of subsequent purification and the introduction of impurities caused by excessive addition.
[0057] In some embodiments, in step S1, the reaction temperature is 45-70°C.
[0058] In a specific embodiment, in step S1, the reaction temperature can be 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C or 70°C.
[0059] When the reaction temperature of step S1 is within the above range, it is beneficial to maintain a high reaction rate of the reaction, while avoiding excessively high temperature that may lead to an increase in the reaction activity of the terminal hydroxyl groups of the hexyl alcohol, thereby causing side reactions.
[0060] In some embodiments, in step S1, the reaction time is 2 to 24 hours.
[0061] In a specific embodiment, in step S1, the reaction time can be 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h or 24 h.
[0062] The reaction time can be adjusted accordingly according to the actual reaction rate. If the reaction time is too short, the reaction yield will be affected, resulting in a waste of raw materials; if the reaction time is too long, the production efficiency will be affected, and there will be no special gain effect on the increase in yield.
[0063] In some embodiments, the carbonate includes one or more of a cyclic carbonate and a chain carbonate. The cyclic carbonate includes ethylene carbonate, and the chain carbonate includes one or more of ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, and diphenyl carbonate.
[0064] In a preferred embodiment, the low alcohol includes methanol.
[0065] In some embodiments, in step S1, after the hexavalent alcohol, alkaline catalyst, carbonate and low-valent alcohol react, the reaction product is concentrated under reduced pressure to precipitate a solid, and the solid is separated and recrystallized to obtain a carbonate polyol.
[0066] The reduced pressure concentration and recrystallization operations are beneficial for purifying the carbonate polyol in the reaction product, avoiding the reaction of unreacted raw materials, alkaline catalysts or by-products with the N,N'-sulfonyldiimidazole in step S2, and reducing the generation of impurities and the consumption of N,N'-sulfonyldiimidazole.
[0067] In some embodiments, the temperature of reduced pressure concentration is 25°C to 45°C.
[0068] In some embodiments, during the recrystallization process, methanol is added to dissolve the solid, and the mass ratio of methanol added for recrystallization to carbonate polyol is 1:1-1:3; then ethyl acetate is slowly added dropwise, and the mass ratio of methanol added for recrystallization to ethyl acetate is 1:5-1:9, preferably 1:6-1:8, to crystallize the carbonate polyol.
[0069] In some embodiments, in step S2, the molar ratio of N,N'-sulfuryldiimidazole to carbonate polyol is 2:1-5:1.
[0070] The preferred molar ratio is 2:1 to 3:1.
[0071] The theoretical reaction molar ratio of N,N'-sulfuryl diimidazole to carbonate polyol is 2:1. Increasing the amount of N,N'-sulfuryl diimidazole added is conducive to ensuring the full reaction of carbonate polyol. At the same time, N,N'-sulfuryl diimidazole has good solubility, and the excess N,N'-sulfuryl diimidazole can be directly separated by solvent stirring and washing to reduce the residual impurities in the final product.
[0072] In some embodiments, the reaction of step S2 is carried out in an aprotic solvent having a dielectric constant less than 8.
[0073] The aprotic solvent with a dielectric constant less than 8 includes, but is not limited to, one or more of ethyl acetate, methyl acetate, ethyl formate, chloroform, ethyl ether, dioxane, furan, dimethyl carbonate, diethyl carbonate, and n-heptane.
[0074] If a solvent with a large dielectric constant is used as the reaction solvent of step S2, the chiral configuration of the reaction product of step S2 will be unstable, and there is a probability that the configuration will be reversed during the reaction process. Therefore, by limiting the dielectric constant of the aprotic solvent, it is beneficial to maintain the stability of the chiral configuration during the reaction process and obtain the compound shown in Structural Formula 2 and / or the compound shown in Structural Formula 3 with higher purity.
[0075] In some embodiments, aprotic solvents with a dielectric constant less than 4 are preferred, such as dioxane, furan, dimethyl carbonate, diethyl carbonate, n-heptane, and the like.
[0076] It should be noted that the dielectric constant refers specifically to the dielectric constant of a substance at 25°C.
[0077] In some embodiments, the mass ratio of the aprotic solvent to N,N'-sulfuryldiimidazole is ≥ 10:1; Because the reaction by-product of step S2 is imidazole, and the dielectric constant of imidazole is greater than 8, there is a probability that the reaction process will cause a configuration reversal. Therefore, it is necessary to increase the amount of aprotic solvent to achieve a dilution effect, reduce the influence of imidazole, and avoid chirality reversal.
[0078] In a preferred embodiment, the mass ratio of the aprotic solvent to N,N'-sulfuryldiimidazole is 10:1 to 30:1.
[0079] In some embodiments, the reaction temperature of step S2 is 25-60° C., and the reaction time is 1-12 h.
[0080] Under the reaction temperature and reaction time conditions, the forward progress of the reaction can be promoted while reducing the occurrence of side reactions.
[0081] In some embodiments, in step S2, after the reaction is completed, the reaction product is stirred and washed, then filtered under reduced pressure, and finally concentrated and dried to remove unreacted N,N'-sulfuryldiimidazole to obtain the target product.
[0082] Another embodiment of the present invention provides a non-aqueous electrolyte solution including a non-aqueous organic solvent, an electrolyte salt, and an additive, wherein the additive includes the cyclic carbonate-sulfate compound as described above.
[0083] Due to the use of the cyclic carbonate-sulfate compound as described above, a uniform and dense solid electrolyte membrane can be formed on the surface of the positive and negative electrodes during the battery formation stage, which can avoid the continuous decomposition of the non-aqueous electrolyte during the battery cycle. The solid electrolyte membrane has high thickness uniformity, has little effect on the deintercalation and extraction of lithium ions, and has high ion conduction efficiency. In particular, the solid electrolyte membrane has excellent high-temperature stability, thereby avoiding the problem of thermal runaway due to structural damage of the positive electrode material under high temperature conditions. At the same time, it also improves the stability of the negative electrode and suppresses the growth of the negative electrode impedance, thereby avoiding the accumulation of heat inside the battery due to excessive impedance, and effectively improving the safety performance of the battery.
[0084] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the cyclic carbonate-sulfate compound is 0.01% to 5%.
[0085] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the cyclic carbonate-sulfate compound can be 0.01%, 0.05%, 0.05%, 0.1%, 0.12%, 0.15%, 0.3%, 0.5%, 0.8%, 0.9%, 1.0%, 1.2%, 1.4%, 1.7%, 1.9%, 2.1%, 2.2%, 2.4%, 2.7%, 2.9%, 3.1%, 3.3%, 3.5%, 3.7%, 4.2%, 4.4%, 4.7%, 4.9% or 5.0%.
[0086] In some embodiments, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound, and a nitrile compound; In a preferred embodiment, the cyclic sulfate ester compound is selected from at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate; The sultone compound is selected from at least one of methylene disulfonate, 1,3-propane sultone, 1,4-butane sultone or 1,3-propene sultone; The cyclic carbonate compound is selected from at least one of vinyl ethylene carbonate, fluoroethylene carbonate or the compound shown in structural formula 6. ; In the structural formula 8, R 21 , R 22 , R 23 , R 24 , R 25 , R 26Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group; The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphate and the compound shown in structural formula 9: ; In the structural formula 9, R 31 , R 32 , R 32 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group.
[0087] In a preferred embodiment, the unsaturated phosphate compound may be at least one of tris(trimethylsilane)phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.
[0088] The borate compound is selected from tris(trimethylsilyl)borate; The nitrile compound is selected from one or more of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0089] In other embodiments, the auxiliary additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.
[0090] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.01% to 30%.
[0091] It should be noted that, unless otherwise specified, in general, the amount of any one of the optional substances in the auxiliary additives added to the non-aqueous electrolyte is less than 10%, preferably, the amount added is 0.1-5%, and more preferably, the amount added is 0.1%~2%. Specifically, the amount of any one of the optional substances in the auxiliary additives can be 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%.
[0092] In some embodiments, when the auxiliary additive is selected from fluoroethylene carbonate, the amount of the fluoroethylene carbonate added is 0.05% to 30% based on the total mass of the non-aqueous electrolyte as 100%.
[0093] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.
[0094] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, or 90%.
[0095] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.
[0096] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but is not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but is not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. There is no particular restriction on the amount of the ether compound added, and it is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more, based on the volume ratio of the non-aqueous solvent being 100%. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.
[0097] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0098] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonate may be, but is not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). The content of the cyclic carbonate is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the conductivity can be reduced due to the reduction in the dielectric constant of the non-aqueous electrolyte, and it is easy to make the large current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery reach a good range. In addition, the upper limit is usually 90% or less by volume, preferably 85% or less by volume, and more preferably 80% or less by volume. By setting this scope, the oxidation / reduction tolerance of nonaqueous electrolyte can be improved, thus contribute to the stability during high temperature storage. The content of linear carbonate is not particularly limited, and relative to the total amount of solvent of nonaqueous electrolyte, it is usually more than 15% by volume, preferably more than 20% by volume, and more preferably more than 25% by volume. In addition, usually the volume ratio is less than 90%, preferably less than 85% by volume, and more preferably less than 80% by volume. By making the content of linear carbonate in the above-mentioned scope, it is easy to make the viscosity of nonaqueous electrolyte reach appropriate range, suppress the reduction of ionic conductivity, and then contribute to make the output characteristics of nonaqueous electrolyte battery reach good scope. When two or more linear carbonates are used in combination, the total amount of linear carbonate is made to meet the above-mentioned scope.
[0099] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.
[0100] The carboxylate solvent includes cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.
[0101] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. There is no special restriction on the amount of sulfone solvent added, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of sulfone solvents can be made to meet the above range. When the amount of sulfone solvent added is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0102] In a preferred embodiment, the non-aqueous organic solvent comprises a mixture of cyclic carbonate and linear carbonate.
[0103] In some embodiments, the electrolyte salt is selected from lithium salts, including LiPF6, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
[0104] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1.0mol / L, 1.1mol / L, 1.15mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.45mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L or 2.5mol / L.
[0105] In other embodiments, if the non-aqueous electrolyte is applied to a sodium ion battery, the electrolyte may also be selected from a corresponding sodium salt.
[0106] Another embodiment of the present invention provides a secondary battery including the nonaqueous electrolyte as described above.
[0107] In some embodiments, the secondary battery is a lithium-ion battery.
[0108] In some embodiments, the positive electrode comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, and the positive electrode active material is selected from LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0109] In a preferred embodiment, the positive electrode active material is selected from LiCoO2.
[0110] LiCoO2 has the highest volume energy density among many positive electrode materials, and has good rate performance. However, as the battery voltage gradually increases, LiCoO2 enters a higher delithiation state, the material structure stability will deteriorate, and the Co in the positive electrode is prone to disproportionation reaction, dissolving in the electrolyte in the form of ions, causing the positive electrode structure to be destroyed, and the risk of thermal runaway is prone to occur under high temperature and high pressure. The cyclic carbonate-sulfate compound provided in the present application, when used in conjunction with LiCoO2, can give full play to the effect of the cyclic carbonate-sulfate compound on the improvement of the material crystal stability of the high-voltage positive electrode, thereby obtaining a lithium-ion battery with both high volume energy density and high safety.
[0111] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.
[0112] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0113] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0114] In some embodiments, the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0115] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.
[0116] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.
[0117] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.
[0118] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0119] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.
[0120] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0121] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0122] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0123] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0124] The present invention is further described below by way of examples.
[0125] Preparation Example 1 Preparation of cyclic carbonate-sulfate compound 1 ⑴. Place 20.0 g of D-mannitol (structural formula 4) and 40.0 mg of potassium carbonate (K2CO3) in a 500 ml three-necked round-bottom flask, then add 60 mL of methanol and heat to 60°C. Add 138.6 mL of dimethyl carbonate (DMC) dropwise under stirring for 30 minutes. After the addition of dimethyl carbonate, heat to 66°C and reflux with stirring for 3 hours to react to generate a crude product of the compound shown in structural formula 6. Afterwards, add 40 mL of methanol to the solid obtained after vacuum concentration, and after complete dissolution, slowly add 200 mL of ethyl acetate (EA) to recrystallize. The generated crystals are filtered under reduced pressure to obtain 14.5 g of the target product. The target product is tested by nuclear magnetic hydrogen spectrum and carbon spectrum, and the test results are as follows: Figure 1 and Figure 2 As shown, the structure was determined to be structural formula 6.
[0126] ⑵. Put 10.0 g of the compound shown in structural formula 6 and 20 g of N,N'-sulfuryl diimidazole into a 250 ml three-necked round-bottom flask, then put in 200 g of diethyl carbonate (dielectric constant 2.82, data source: Solvent Handbook), and heat to 60°C. The reaction time is 6 hours, and the reaction progress is monitored by TLC. After the reaction is completed, 20 mL of water is added for multiple washings, and then the solid obtained after vacuum concentration is added with 20 mL of diethyl carbonate for slurrying, the temperature is controlled at 5 degrees Celsius, the stirring time is 0.5 hours, and vacuum filtration is performed, and concentrated and dried to obtain 11.5 g of cyclic carbonate-sulfate compound 1.
[0127] (3) The obtained cyclic carbonate-sulfate compound 1 was subjected to liquid chromatography test, and the mass content of the compound shown in Chemical Formula 1 in the cyclic carbonate-sulfate compound was 99%. The organic impurity content was 1%. The chlorine content of the compound tested by turbidimetry was 100 ppm.
[0128] At the same time, the obtained cyclic carbonate-sulfate compound was dissolved in acetonitrile and injected, and chromatographic testing was performed using high performance liquid chromatography (instrument: Agilent 1200 series high performance liquid chromatography system, Waters ultra-high performance convergence chromatography system, column temperature: 25°C; flow rate: 1.0 mL / min.), and the single configuration content of the compound shown in Chemical Formula 1 in the obtained cyclic carbonate-sulfate compound 1 was 99%. The ratio of stereoisomer impurities to the compound shown in Chemical Formula 1 was 1%.
[0129] Further, the obtained cyclic carbonate-sulfate compound was tested for H NMR spectrum and C NMR spectrum using deuterated acetonitrile and deuterated DMSO, respectively. The test results are as follows: Figure 3~Figure 6 As shown, the structure is determined to be chemical formula 1; according to the NMR carbon spectrum Figure 4 and Figure 6, except for the carbonyl carbon, there are only 3 chemical environment carbons instead of 6, and the obtained compound of Chemical Formula 1 has a single configuration axisymmetry.
[0130] Furthermore, the cyclic carbonate-sulfate compound 1 was cultured into a single crystal and the crystal was tested by single crystal X-ray diffraction (XRD) under the following test conditions: T = 100.0(2) K, μ(GaKα) = 3.126 mm -1 , get the measured Figure 7 With the measured Figure 8 :The crystal belongs to the monoclinic system, space group: P21, crystal parameters: a=9.0824(12) Å, b=6.3730(8) Å, c=10.1036(13)Å, β= 93.744(4)°, V = 583.57(13) Å 3 , Z=2, and after data processing, we get the following Table 1.
[0131] Table 1 Crystal structure data table
[0132] like Figure 7 and Figure 8 As shown, the compound shown in Structural Formula 2 is a monoclinic system, which is characterized by no high-order symmetry axis, the b axis is the only axis, and there are no more than one secondary symmetry axis and symmetry plane. The b axis is orthogonal to the a axis and the c axis, while the a axis is oblique to the c axis, with an axis angle of α=γ=90°, β≠90°, and an axis unit of a≠b≠c. And the space group of Structural Formula 2 is P21, and its symmetry elements include a two-fold rotation axis and a slip plane, that is, the symmetry operation of Structural Formula 2 includes a two-fold rotation around the b axis and a slip plane perpendicular to the b axis. The single crystal spatial structure is determined to be Structural Formula 2.
[0133] Furthermore, the cyclic carbonate-sulfate compound 1 was subjected to a powder diffraction test and compared with the single crystal X-ray simulated diffraction, and the obtained Fig. 9 , indicating that the spatial structure of the obtained cyclic carbonate-sulfate compound is consistent with its single crystal spatial configuration. The spatial structure of the cyclic carbonate-sulfate compound is determined to be structural formula 2.
[0134] Further, the specific rotation of cyclic carbonate-sulfate compound 1 was tested according to the following method: Weigh 5g of cyclic carbonate-sulfate compound 1, dissolve it completely in acetonitrile (acetonitrile purity>99%, water content<1000ppm) to prepare a solution, the concentration of cyclic carbonate-sulfate compound 1 is 0.126g / mL. Test according to "GBT613-2007 General Test Method for Determination of Specific Rotation of Chemical Reagents (Specific Rotation)", test conditions: wavelength 589nm, temperature 20 degrees Celsius, solvent acetonitrile, test tube length 100mm, concentration 0.126g / mL. Specific rotation [ α ] = -7.982°∙mL / (dm∙g), abbreviated as specific rotation [ α ]=-7.982.
[0135] In summary, the cyclic carbonate-sulfate compound 1 is obtained: the mass content of the compound shown in Chemical Formula 1 is 99% (the mass ratio of the compound shown in Structural Formula 2 to the compound shown in Chemical Formula 1 is 99%, and the mass ratio of the stereoisomer impurity to the compound shown in Chemical Formula 1 is 1%). The mass content of organic impurities is 1%. The chlorine content of the compound tested by turbidimetry is 100 ppm.
[0136] Furthermore, cyclic carbonate-sulfate compounds of different purities can be obtained by recrystallization (natural crystallization in a mixed solvent of acetonitrile and ethyl acetate) or high performance liquid chromatography preparative separation gradient elution, batch collection and concentration, and further purification and separation. The influence of the specific rotation of the cyclic carbonate-sulfate compounds on the proportion of structural formula 2 was tested, and Table 2 was obtained.
[0137] Test conditions: wavelength 589 nm, temperature 20 degrees Celsius, solvent acetonitrile, test tube length 100 mm, concentration of cyclic carbonate-sulfate compound 0.126 g / mL.
[0138] Table 2
[0139] Preparation Example 2 Preparation of cyclic carbonate-sulfate compound 2 Cyclic carbonate-sulfate compound 2 was obtained by further purifying the cyclic carbonate-sulfate compound 1 obtained in Preparation Example 1.
[0140] Cyclic carbonate-sulfate compound 2: The mass content of the compound shown in Chemical Formula 1 is 99.8% (the mass ratio of the compound shown in Structural Formula 2 to the compound shown in Chemical Formula 1 is 99.8%, and the mass ratio of the stereoisomer impurity to the compound shown in Chemical Formula 1 is 0.2%). The mass content of organic impurities is 0.2%. The chlorine content of the compound tested by turbidimetry is 10ppm. The specific optical rotation is -7.311°∙mL / (dm∙g).
[0141] The specific rotation test conditions were: wavelength 589 nm, temperature 20 degrees Celsius, solvent acetonitrile, test tube length 100 mm, and concentration of cyclic carbonate-sulfate compound 0.126 g / mL.
[0142] Preparation Example 3 Preparation of cyclic carbonate-sulfate compound 3 The method includes most of the steps in Preparation Example 1, except that: L-mannitol (Structural Formula 5) is used instead of D-mannitol (Structural Formula 4); and the NMR test results are as follows: Fig.10 and Fig.11 .
[0143] The obtained cyclic carbonate-sulfate compound 3 has the following content: the content of chemical formula 1 is 99.6% (the ratio of structural formula 3 to the compound of chemical formula 1 is 99.4%, and the ratio of stereoisomer impurities to the compound of chemical formula 1 is 0.6%). The content of organic impurities is 0.4%. The chlorine content of the compound tested by turbidimetry is 100 ppm. The specific optical rotation is +7.546°∙mL / (dm∙g).
[0144] Test conditions: wavelength 589 nm, temperature 20 degrees Celsius, solvent acetonitrile, test tube length 100 mm, concentration of cyclic carbonate-sulfate compound 0.126 g / mL.
[0145] Preparation Example 4 Preparation of cyclic carbonate-sulfate compound 4 Among them, cyclic carbonate-sulfate compound 4 is obtained by completely dissolving cyclic carbonate-sulfate compound 1 and cyclic carbonate-sulfate compound 3 in acetonitrile, mixing them in a mass ratio of 1 / 1 and then concentrating them under reduced pressure. The specific rotation is +0.021°∙mL / (dm∙g). The specific rotation test conditions are: test temperature 20 degrees Celsius, wavelength 589nm, test tube length 100mm, solvent acetonitrile, and cyclic carbonate-sulfate compound concentration 0.126g / mL.
[0146] Preparation Example 5 The method includes most of the operations in Preparation Example 1, except that: Acetonitrile (dielectric constant 37.5) was used instead of diethyl carbonate in Example 1.
[0147] A cyclic carbonate-sulfate compound 5 was obtained, in which the mass content of the compound represented by chemical formula 1 was 99% (the mass ratio of the compound represented by structural formula 2 to the compound represented by chemical formula 1 was 65%, and the mass ratio of the stereoisomer impurity to the compound represented by chemical formula 1 was 35%). The mass content of organic impurities was 1%. The chlorine content of the compound tested by turbidimetry was 100 ppm. The specific optical rotation was -8.575°∙mL / (dm∙g).
[0148] The specific rotation test conditions were: wavelength 589 nm, temperature 20 degrees Celsius, solvent acetonitrile, test tube length 100 mm, and concentration of cyclic carbonate-sulfate compound 0.126 g / mL.
[0149] Preparation Example 6 Preparation of cyclic carbonate-sulfate compound 6 ⑴. Put 20.0 g of D-mannitol and 40.0 mg of potassium carbonate (K2CO3) into a 500 ml three-necked round-bottom flask, then put in 60 mL of methanol and heat to 60°C. Add 138.6 mL of dimethyl carbonate (DMC) dropwise under stirring for 30 minutes. After the addition of dimethyl carbonate, heat to 66°C, reflux and stir for 3 hours to react, and generate a crude product of the compound shown in structural formula 4. After that, add 40 mL of methanol to the solid obtained after vacuum concentration, and after complete dissolution, slowly add 200 mL of ethyl acetate (EA) to recrystallize. Filter the generated crystals under vacuum to obtain 14.6 g of intermediate product 1.
[0150] ⑵, put 10.0 grams of intermediate product 1 and 12 grams of thionyl chloride into a 250 ml three-necked round-bottom flask, then put in 100 g of dichloromethane and heat to 60 ° C. Reflux reaction time is 6 hours. Vent reaction, tail gas absorption until no gas is generated. After that, add 20 mL of diethyl carbonate to the solid obtained after vacuum concentration for pulping, control the temperature at 5 degrees Celsius, stir for 0.5 hours, perform vacuum filtration, concentrate and dry to obtain 11.5 grams of intermediate product 2.
[0151] (3) 10.0 g of intermediate product 2 and 100 g of acetonitrile were placed in a 250 ml three-necked round-bottom flask, and the temperature was controlled at 10-15 degrees Celsius. 10 g of 40% hydrogen peroxide was added dropwise, and the temperature during the addition process was controlled to be less than 35 degrees Celsius. The stirring reaction time was 6 hours. After that, the mixture was filtered under reduced pressure, concentrated and dried to obtain 8.23 g of a cyclic carbonate-sulfate compound.
[0152] After testing, the content of the compound shown in Chemical Formula 1 in the cyclic carbonate-sulfate compound 6 is 99.7% (the ratio of the structural formula 2 / 3 to the compound shown in Chemical Formula 1 is <1%, and the mass ratio of the stereoisomer impurities to the compound shown in Chemical Formula 1 is 99%). The mass content of organic impurities is 0.3%. The chlorine content of the compound tested by turbidimetry is 100ppm. The specific optical rotation is -9.731°∙mL / (dm∙g). The specific optical rotation test conditions are: test temperature 20 degrees Celsius, wavelength 589nm, test tube length 100mm, solvent acetonitrile, and carbonate-sulfate compound concentration 0.126g / mL.
[0153] Examples 1 to 9, Comparative Examples 1 to 3 1) Preparation of non-aqueous electrolyte Ethylene carbonate (EC) and diethyl carbonate (DEC) are uniformly mixed in a weight ratio of 30:70, LiPF6 is added to 1.15 mol / L, and then the cyclic carbonate-sulfate compound prepared above is added and dissolved in the above non-aqueous organic solvent to obtain a non-aqueous electrolyte. The selection of the cyclic carbonate-sulfate compound in each embodiment and each comparative example and the content in the non-aqueous electrolyte are shown in Table 3, and the content is calculated as a percentage of the total mass of the non-aqueous electrolyte.
[0154] 2) Preparation of positive electrode The positive electrode active material LiCoO2, conductive carbon black and binder PVDF are dispersed in a non-aqueous organic solvent NMP (N-methyl-2-pyrrolidone) and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, and after drying, rolling and cutting, a positive electrode sheet is obtained. The weight ratio of the positive electrode active material, conductive carbon black and binder PVDF is 95:3:2.
[0155] 3) Preparation of negative electrode sheet The negative electrode active material graphite, conductive agent, CMC and SBR are dispersed in deionized water at a weight ratio of 95:2:1:2 and stirred to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, and after drying, rolling and cutting, a negative electrode sheet is obtained.
[0156] 4) Preparation of lithium-ion batteries The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence using the lamination process, and then a soft-pack battery is made after processes such as top and side sealing and injection of non-aqueous electrolyte.
[0157] 5) Formation The formation was carried out in the following steps: 0.05C constant current charging for 180 min, 0.1C constant current charging for 180 min, and then shaped and sealed after 24 hours of storage. Then, the battery was further charged at 0.2C constant current to 100% SOC. After 24 hours of storage at room temperature, it was discharged at 0.2C constant current to 3.0V.
[0158] Performance Testing 1. The lithium-ion batteries prepared in Example 3 and Comparative Example 2 were disassembled in a glove box filled with argon gas to obtain the positive electrode sheets. The obtained positive electrode sheets were cut into test samples of 8 mm × 8 mm in size, and soaked and cleaned with a low-boiling-point dimethyl carbonate DMC solvent for half an hour. After being completely dried, they were imaged with a transmission electron microscope (TEM). The test results are as follows: Fig.12As shown, "Fresh" is a positive electrode sheet that has not been formed and cycled, "Example 3" is the test result of Example 3; "Comparative Example 2" is the test result of Comparative Example 2. It can be seen from the test results that the solid electrolyte membrane on the surface of the positive electrode in Comparative Example 2 obviously has the problem of uneven thickness, with thicker thickness in some positions and thinner thickness in some positions. The thicker positions will increase the battery impedance, and the thinner positions will have protection defects, thereby continuously consuming the electrolyte, resulting in a decrease in the battery cycle life. In Example 3, the thickness of the solid electrolyte membrane on the surface of the positive electrode is relatively uniform, and the thickness difference at each position is not large, which can achieve a better protection effect for the positive electrode material; it shows that compared with the cyclic carbonate-sulfate compound 6 in Comparative Example 2, the solid electrolyte membrane formed by the cyclic carbonate-sulfate compound 1 provided in Example 1 has higher density and uniformity, can be evenly distributed on the surface of the positive electrode material, thereby inhibiting the continuous growth of the positive electrode surface impedance, and avoiding the continuous consumption of the electrolyte on the positive electrode surface during the battery cycle.
[0159] The positive electrode sheets of Example 3 and Comparative Example 2 were reassembled into batteries and subjected to 300 charge and discharge cycles. The positive electrode sheets were then taken out for phase transformation observation. The results were as follows: Fig.12 As shown by Fig.12 It can be seen that the positive electrode particles of Example 3 maintain a good layered structure, while the comparative example 2 undergoes a phase transition, loses the crystal structure of the material itself, and exhibits a salt rock phase.
[0160] 2. The batteries obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were subjected to the following tests: 1. Hot box safety performance test: The formed battery is charged to 4.5V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C, and then discharged to 3.0V at a constant current of 0.5C. The battery is cycled 5 times at room temperature 25℃ in this procedure, and the battery discharge capacity is calculated. If the discharge capacity deviation is ±10mAh / g, the battery is charged to 4.5V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C, which is regarded as the fully charged state of the battery. The fully charged battery is placed in the GX-3020-BL40 thermal shock test chamber, and the hot box works according to the set program "heating from 25℃ to 130℃ at 5℃ / min and maintaining for 30min", and the temperature channel and voltage channel of the "data acquisition instrument" panel start to record real-time data. During the test, the battery surface temperature detected by the data acquisition instrument does not exceed 200℃, the voltage drop does not exceed 0.3V, and the battery does not explode or catch fire. The hot box passes OK, otherwise it is NG. Record the highest temperature value of the battery table and take the average value. There are 10 batteries in each group.
[0161] 2. High temperature cycle performance test: The formed battery is placed in a constant temperature oven at 45°C, charged to 100% SOC at a constant current of 1C, and then discharged to 3.0V at a constant current of 1C. This cycle is repeated 500 times, and the first discharge capacity and the last discharge capacity are recorded.
[0162] The capacity retention rate of high temperature cycle is calculated as follows: Capacity retention rate = last discharge capacity / first discharge capacity × 100%.
[0163] Impedance growth rate = (last impedance - first impedance) / first impedance × 100% 3. High temperature storage performance test: The formed battery is charged to 4.5V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C, then discharged to 3.0V at a constant current of 0.5C, and the initial discharge capacity is recorded. Then, the battery is charged to 4.5V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C. The initial volume of the battery is determined by the drainage method, and then stored at 60°C for 30 days. After the battery is cooled to room temperature, the volume after storage is tested, and the battery retention capacity is measured by discharging to 3.0V at a constant current of 0.5C. The calculation formula is as follows: Capacity retention rate (%) = retention capacity / initial discharge capacity × 100%; Expansion rate (%) = (volume after storage - initial volume) / initial volume × 100%; The test results are recorded in Table 3: Table 3
[0164] It can be seen from the test results of Examples 1 to 9 and Comparative Examples 1 to 3 that, compared with the cyclic carbonate-sulfate compounds 5 and cyclic carbonate-sulfate compounds 6 having specific rotations outside the range of -7.982°∙mL / (dm∙g) to +7.982°∙mL / (dm∙g), the cyclic carbonate-sulfate compounds 1 to 4 having specific rotations within the range of -7.982°∙mL / (dm∙g) to +7.982°∙mL / (dm∙g) can be used as electrolyte additives for lithium-ion batteries. The high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery can be significantly improved, especially the effect of improving the thermal shock resistance of the lithium-ion battery and inhibiting the impedance growth is particularly obvious, indicating that the compound represented by the axially symmetrical structural formula 2 and the compound represented by the structural formula 3 have a significant gain effect on improving the film quality in the process of battery formation to form an SEI or CEI film.
[0165] By comparing the test results of Example 2 and Example 5, and Example 3 and Comparative Example 1, it can be seen that the film-forming quality of the cyclic carbonate-sulfate compound is greatly affected by the purity of a single chiral configuration in the compound. When the purity of the compound shown in Structural Formula 2 in the cyclic carbonate-sulfate compound is at a high level, the high temperature performance and thermal shock resistance of the lithium-ion battery can be significantly improved, and the impedance of the lithium-ion battery can be reduced.
[0166] By comparing the test results of Examples 1, 2, 4 and Examples 7 to 9, it can be seen that when the compound represented by Chemical Formula 1 mainly contains the compound represented by Structural Formula 2 and / or the compound represented by Structural Formula 3, when the characteristic structural compound is selected from a single chiral configuration (the compound represented by Structural Formula 2 or the compound represented by Structural Formula 3), it is more conducive to improving the thermal shock resistance of the formed solid electrolyte membrane, indicating that the characteristic structural compound with a single chiral configuration is related to improving the orderliness of the solid electrolyte membrane.
[0167] Examples 10-18, Comparative Examples 4-6 1) Preparation of non-aqueous electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of EC:DEC:EMC=1:1:1, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and then a cyclic carbonate-sulfate compound is added as an additive. The selection of the cyclic carbonate-sulfate compound in each embodiment and each comparative example and the content in the non-aqueous electrolyte are shown in Table 4, and the content is calculated as a percentage of the total mass of the non-aqueous electrolyte.
[0168] 2) Preparation of positive plate: Mixed positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2, conductive carbon black Super-P and polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. Aluminum foil is used as the positive electrode current collector, and the slurry is evenly coated on both sides of the aluminum foil. After drying, calendering and vacuum drying, the positive electrode material layer is obtained, and the aluminum lead wire is welded with an ultrasonic welder to obtain the positive electrode plate.
[0169] 3) Preparation of negative plate: The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled and vacuum dried, and a nickel lead wire was welded with an ultrasonic welder to obtain a negative electrode plate.
[0170] 4) Preparation of battery cells: A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate. The porosity of the separator is shown in Table 2. Then, the sandwich structure consisting of the positive plate, the negative plate and the separator was wound, and the wound body was flattened and placed in an aluminum foil packaging bag. It was vacuum baked at 85°C for 48 hours to obtain a battery cell to be injected with liquid.
[0171] 5) Battery filling and formation: In a glove box with a dew point controlled below -40°C, the non-aqueous electrolyte prepared above was injected into the battery cell, vacuum packaged, and left to stand for 24 hours.
[0172] Then, the conventional formation of the first charge was carried out according to the following steps: 0.1C constant current charging for 45 min, 0.2C constant current charging for 30 min, 0.5C constant current charging for 75 min, secondary vacuum sealing, and then further charging to 4.4 V at 0.5C constant current, and then constant voltage charging until the current drops to 0.02 C, after standing for 5 min, and then discharging to 3.0 V at 0.5C constant current to obtain a LiNi 0.5 Co 0.2 Mn 0.3 O2 / artificial graphite lithium-ion battery.
[0173] Performance Testing The following tests were performed on the batteries obtained in Examples 10 to 18 and Comparative Examples 4 to 6: 1. Hot box safety performance test: The formed battery is charged to 4.4V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C, and then discharged to 3.0V at a constant current of 0.5C. The battery is cycled 5 times at room temperature 25℃ in this procedure, and the battery discharge capacity is calculated. The discharge capacity deviation is ± 10mAh / g, then the battery is charged to 4.4V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C, which is regarded as the fully charged state of the battery. The fully charged battery is placed in the GX-3020-BL40 thermal shock test chamber, and the hot box works according to the set program "heating from 25℃ to 130℃ at 5℃ / min and maintaining for 30min", and the temperature channel and voltage channel of the "data acquisition instrument" panel start to record real-time data. During the test, the battery surface temperature detected by the data acquisition instrument does not exceed 200℃, the voltage drop does not exceed 0.3V, and the battery does not explode or catch fire. The hot box passes OK, otherwise it is NG. Record the highest temperature value of the battery table and take the average value. There are 10 batteries in each group.
[0174] 2. High temperature cycle performance test: The formed battery is placed in a constant temperature oven at 45°C, charged to 100% SOC at a constant current of 1C, and then discharged to 3.0V at a constant current of 1C. This cycle is repeated for 500 times, and the first discharge capacity, the first impedance, the last impedance and the last discharge capacity are recorded.
[0175] The capacity retention rate of high temperature cycle is calculated as follows: Capacity retention rate = last discharge capacity / first discharge capacity × 100%.
[0176] Impedance growth rate = (last impedance - first impedance) / first impedance × 100%.
[0177] 3. High temperature storage performance test: The formed battery is charged to 4.4V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C, then discharged to 3.0V at a constant current of 0.5C, and the initial discharge capacity is recorded. Then, the battery is charged to 4.4V at a constant current of 0.5C and then charged at a constant voltage until the current drops to 0.03C. The initial volume of the battery is determined by the drainage method, and then stored at 60℃ for 30 days. After the battery is cooled to room temperature, the volume after storage is tested, and the battery retention capacity is measured by discharging to 3.0V at a constant current of 0.5C. The calculation formula is as follows: Capacity retention rate (%) = retention capacity / initial discharge capacity × 100%; Expansion rate (%) = (volume after storage - initial volume) / initial volume × 100%; The test results obtained are recorded in Table 4: Table 4
[0178] It can be seen from the test results of Examples 10 to 18 and Comparative Examples 4 to 6 that, compared with the cyclic carbonate-sulfate compounds 5 and cyclic carbonate-sulfate compounds 6 having specific rotations outside the range of -7.982°∙mL / (dm∙g) to +7.982°∙mL / (dm∙g), the cyclic carbonate-sulfate compounds 1 to 4 having specific rotations within the range of -7.982°∙mL / (dm∙g) to +7.982°∙mL / (dm∙g) can be used as electrolyte additives for lithium-ion batteries. The high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery can be significantly improved, especially the effect of improving the thermal shock resistance of the lithium-ion battery and inhibiting the impedance growth is particularly obvious, indicating that the compound represented by the axially symmetrical structural formula 2 and the compound represented by the structural formula 3 have a significant gain effect on improving the film quality in the process of battery formation to form an SEI or CEI film.
[0179] By comparing the test results of Example 11 and Example 14, and Example 12 and Comparative Example 4, it can be seen that the film-forming quality of the cyclic carbonate-sulfate compound is greatly affected by the purity of a single chiral configuration in the compound. When the purity of the compound shown in Structural Formula 2 in the cyclic carbonate-sulfate compound is at a high level, the high temperature performance and thermal shock resistance of the lithium-ion battery can be significantly improved, and the impedance of the lithium-ion battery can be reduced.
[0180] By comparing the test results of Examples 10, 11, 13 and Examples 16 to 18, it can be seen that when the compound represented by Chemical Formula 1 mainly contains the compound represented by Structural Formula 2 and / or the compound represented by Structural Formula 3, when the characteristic structural compound is selected from a single chiral configuration (the compound represented by Structural Formula 2 or the compound represented by Structural Formula 3), it is more conducive to improving the thermal shock resistance of the formed solid electrolyte membrane, indicating that the characteristic structural compound with a single chiral configuration is related to improving the orderliness of the solid electrolyte membrane.
[0181] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A cyclic carbonate-sulfate compound, characterized in that The cyclic carbonate-sulfate compound includes a compound shown in Chemical Formula 1, and the specific rotation of the cyclic carbonate-sulfate compound is [ α ] is -7.982°∙mL / (dm∙g)~+7.982°∙mL / (dm∙g); 。 2. The cyclic carbonate-sulfate compound according to claim 1, characterized in that The compound represented by the chemical formula 1 includes a characteristic structure compound, and the characteristic structure compound is selected from the compound represented by the structural formula 2 and / or the compound represented by the structural formula 3, and the content of the characteristic structure compound in the compound represented by the chemical formula 1 is ≥99wt%; 。 3. The cyclic carbonate-sulfate compound according to claim 2, characterized in that The characteristic structure compound is selected from the compound shown in structural formula 2.
4. The cyclic carbonate-sulfate compound according to claim 2, characterized in that The characteristic structure compound is selected from the compound shown in structural formula 3.
5. The cyclic carbonate-sulfate compound according to claim 1, characterized in that The specific rotation [ α ] The test conditions are: wavelength of 589nm, temperature of 20 degrees Celsius, solvent of acetonitrile, test tube length of 100mm, and concentration of cyclic carbonate-sulfate compound of 0.126g / mL.
6. The cyclic carbonate-sulfate compound according to claim 2, characterized in that The cyclic carbonate-sulfate compound satisfies at least one of the following conditions: (I) In the cyclic carbonate-sulfate compound, the content of the compound represented by Chemical Formula 1 is ≥ 99 wt %; (II) The compound represented by the chemical formula 1 also includes stereoisomer impurities other than the characteristic structure compound, and the content of the stereoisomer impurities in the compound represented by the chemical formula 1 is ≤1wt%; (III) The content of chlorine in the cyclic carbonate-sulfate compound is ≤100 ppm.
7. The cyclic carbonate-sulfate compound according to claim 1, characterized in that The cyclic carbonate-sulfate compound further includes organic impurities, the mass content of the organic impurities is ≤1wt%, and the organic impurities include one or more of the following compounds: 。 8. Use of the cyclic carbonate-sulfate compound according to any one of claims 1 to 7 as an electrolyte additive.
9. A non-aqueous electrolyte, characterized in that The invention comprises a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises the cyclic carbonate-sulfate compound according to any one of claims 1 to 8.
10. The non-aqueous electrolyte according to claim 9, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the cyclic carbonate-sulfate compound is 0.01% to 5%.
11. A secondary battery, characterized in that: Comprising the non-aqueous electrolyte as claimed in claim 9 or 10.
Citation Information
Patent Citations
Lithium ion battery electrolyte additive cyclic ethylene carbonate sulfate and preparation method thereof
CN111755753A
Polyol carbonate bisulfate compound and preparation method thereof
CN118184644A
Polycyclic compound, preparation method and application thereof, electrolyte and battery
CN118307530A
Polycyclic compound, preparation method and application thereof, electrolyte and battery
CN118307531A
Polycyclic compound, preparation method and application thereof, electrolyte and battery
CN118666825A
Cited By
Preparation method of mannitol carbonate sulfate
CN120441561A
Preparation method of ethylene bisulfate and ethylene carbonate
CN121873054A
A method for preparing ethylene disulfate and ethylene bicarbonate
CN121873054B
Process for the preparation of cyclic carbonate disulfate compounds
CN122749500A
Polycyclic compound, and preparation method therefor and use thereof, electrolyte, and battery
WO2025256531A1
